The Oxford handbook of Latin American political economy - Santiso, Javier; Dayton-Johnson, Jeff. (New York ; Oxford : Oxford University Press, 2012)
Understanding Latin America's recent economic performance calls for a multidisciplinary analysis. This handbook looks at the interaction of economics and politics in the region and includes a number of contributions from top academic experts who have also served as key policy makers, reflecting upon the challenges of reform.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Latin America -- Economic policy; Latin America -- Economic conditions -- 1982-; Latin America -- Politics and government -- 1980-; Latin America. -- Economic policy; Latin America. -- Economic conditions. -- 1982-; Latin America. -- Politics and government. -- 1980-